Suprasellar Mature Cystic Teratoma Mimicking Rathke’s Cleft Cyst: A Case Report and Systematic Review of the Literature - Jiang, Shenzhong; Wang, Zhaojian; You, Yan; Wang, Renzhi; Bao, Xinjie (Frontiers in Endocrinology, 2021)
In this article, we present a 31-year-old female who presented with intermittent headache, oligomenorrhea of over 10 years’ duration. Imaging revealed a large suprasellar mass with sellar extension. The patient underwent an endoscopic endonasal trans-sphenoidal surgery for resection of the mass. Clinical, radiological and operative findings of this patient were initially considered as Rathke’s cleft cyst (RCC). However, post-operative histological examinations disclosed a mature cystic teratoma. No radiotherapy was performed after surgery. At the most recent follow-up, approximately 1 year later, the patient is doing well with no headache and no recurrence of the teratoma.